Development of Ar Interactive Learning Media on Ecosystem Material to Improve Critical Thinking Abilities in Grade V Students - Azizah Nur Avivah; Suttrisno; Nurul Mahruzah Yulia (Journal of Practice Learning and Educational Development, 2025)
The lack of use of digital-based learning media causes the social studies learning process to be less than optimal, in addition, in the initial research the critical thinking skills of students in class V of MI Al-Ma'had Roudlotul Huda were low, so the researcher developed augmented reality learning media. The purpose of this study is to develop AR-based digital learning media in IPAS subjects to improve the critical thinking skills of students in class V of MI Al-Ma'had Roudlotul Huda. This research uses the Research and Development research method, with the ADDIE development model: analysis, design, development, implementation, evaluation. This study involved 20 students in class V. The results of the study explained that the augmented reality learning media developed was suitable for use, as evidenced by the validation results of material experts of 93% and media experts of 91%. The results of the product test in the pre-test stage showed a percentage of 63.3% in the "medium" category, while in the post-test stage it showed a percentage of 92% in the "high" category. Furthermore, the results of the pre-test and post-test were analyzed with the N-Gain formula, and the result was 0.74 with the category of "high improvement". Based on these results, it is stated that augmented reality learning media shows that it is very feasible to use in the learning process. In addition, augmented reality learning media has proven to be very effective in helping students understand, analyze, and draw conclusions by relating to everyday experiences.